WORK WITHOUT LABOR: Life in the Surround of a Rural Prison Town. (3rd June 2021) - PEARSON, HEATH
ABSTRACT: This article challenges the idea that the U.S. prison boom is a federally driven fix. By assembling a two‐hundred‐year regional history of Cliptown, New Jersey—a rural town with five prisons and three police departments—the article indicates that prisons appear not as an external fix but as the most recent technological iteration of a homegrown system that has always functioned to capture labor through white supremacist domination. Locally historicizing the evolution of this dominating system, however, refuses to concede the final word to prisons and earlier confinement technologies, concluding, instead, in an alternative space that exceeds the capture of confinement, where formerly incarcerated people collaborate to expand freedoms and to practice being unavailable for confinement's servitude.